THE ROLE OF RELATIONSHIP MANAGEMENT IN THE SUCCESSFUL OUTSOURCING OF MAINTENANCE - van Niekerk, A. J.; Visser, J. K. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: Outsourcing some maintenance functions (or the entire maintenance of specific equipment) is one of the options available to maintenance managers in managing their department more effectively. Several factors should be considered in establishing an outsourced maintenance relationship with the potential for long-term success. This paper discusses the results of an investigation into the role of relationship management in the success of maintenance outsourcing by users of production facilities. The results of a survey in the process industry reveal a strong correlation between successful outsourced maintenance and proper on-going management of the outsourcing relationship, and indicate that shortcomings in the management of the relationship are a prime driver of failed maintenance outsourcing. AFRIKAANSE OPSOMMING: Die uitkontraktering van sommige instandhoudingstake (of die totale instandhouding van spesifieke toerusting) is een van die opsies wat die instandhoudingsbestuurder kan oorweeg om